AN IMPLICATION ANALYSIS OF SEXUALITY IN THAI CONTEMPORARY ART: A CASE STUDY OF THE WORK OF PRATEEP KOCHABUA AND LUMPOO KASANAU - Siriratchaneekorn, Supoj (Fine Arts Journal: Srinakharinwirot University, 2021)
This study aims to present the mythical signifier which is expressed through Thai contemporary art. It generally presents itself through stories, contexts, ideals, conservative traditions and cultures where the aspects of patriarchy ideology are presented. This perspective is presented through the pieces of artwork that attempt to conceal and expel other less important concepts, especially the sexuality between males and females in Thai society. The messages about patriarchy are rooted in many aspects of Thai society. This article investigates and analyses two portraits of Thai contemporary artists. The first portrait named “Luang Ta Ma (Traditional Thai Music) was painted by Prateep Kochabua, and the second portrait named “The Presents” was painted by Lumpoo Kansanau. These two portraits are regarded as the representative of Thai contemporary art. This article aims to analyze the implications of sexuality in order to decode or justify the implications of the mythical signifier which is implicitly expressed through these two portraits. The two portraits were analyzed through two steps of decoding. The first step was to interpret the denotative and connotative meanings expressed through the portraits. The second step was to analyze the meaning based on the feminism concepts about aspects of psychoanalysis, dualism, space, gazing, and body appearance. The results of the study reveal that these two portraits represent Thai traditions and ways of life. They also indicate that Thai people are friendly, generous, humble, and kind. In addition, these two portraits present the mythical signifier regarding the aspects of friendliness, warmness, and the relationships among elderly people through the realistic art. According to the results from the sexuality analysis on these two portraits, the different interpretations and meanings were observed. These two portraits present the implication that female roles are only limited to the obligations of being a mother, wife and “what a Thai female has to follow” according to Thai culture and customs. Consequently, these two portraits have repeatedly emphasized the messages about the power of Thai males over Thai females. They also reflect the aspects of Thai society through the mythical signifiers in Thai contemporary art.